Sediment Analysis in the Way Besai Hydroelectric Watershed Using the USLE Method (United Soil Loss Equation) - Rahmawati, Fitriya; Winarno, Dwi Joko; Kusumastuti, Dyah Indriana (Universitas Lampung, 2018)
Way Besai hydropower station is located in Way Besai river basin (watershed) with most watersheds surrounded by mountains that cause erosion resulting in sediment buildup. The purpose of this research is to know the degree of erosion hazard and to know the sediment by the Universal Soil Loss Equation (USLE) method in Way Besai Watershed. The location of this research was conducted at Way Besai Sub River Watershed, Tulang Bawang Watershed, West Lampung Regency with Way Petai as the control point. The data needed in this research is the limitation of Way Besai Watershed catchment, land use data and land type at Way Besai Watershed catchment area. From the result of sedimentation analysis with USLE method, it can be known that the erosion rate of Way Besai Watershed catchment area is 305.03 ton/ha/year which is classified as Class IV Hazard Erosion or heavy and sedimentation of Way Besai Watershed catchment area is 165.079,13 ton/year.